Rancang Bangun Sistem Pengering Bengkuang Sebagai Olahan Keripik Berbasis Mikrokontroler - Yelchi Multri Meisya; Dodon Yendri (Universitas Andalas, 2022)
This research was conducted with the aim of drying jicama as a processed yam chips. The condition of the yam dried in an open space with low temperatures resulted in the growth of fungus on the surface of the jicama. The growth of mushrooms on jicama makes it unable to be processed and consumed. Therefore we need a system that can dry yam with a drying machine. This system can monitor the water content of jicama using a soilmoisture sensor and measure the temperature with the DS18B20 sensor in the drying room. Jicama is said to be dry when the water content is <10%, when the moisture content value (> 25%) then the jicama is wet, if the water content of the jicama (10.1% ≤ KA ≤ 25%) then the jicama is in a humid condition, so that the fan, heater and DC motor turns on. This tool is designed using the Arduino Uno, DS18B20 sensor, Soilmoiture sensor, heater, DC fan, DC motor, buzzer, relay, LCD. When the temperature is> 60 ° C, the DC Heater and Fan will turn off to reduce the temperature. The results of the yam condition will be displayed on the LCD. This is expected to be able to dry jicama quickly and produce dry jicama with good quality.